Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1080/00498250412331285481
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical-induced changes in gene expression of carcinogen-metabolizing enzymes in cultured human primary hepatocytes

Abstract: 1. The naturally occurring compounds curcumin (CUR), 3,3'-diindolylmethane (DIM), isoxanthohumol (IXN), 8-prenylnaringenin (8PN), phenethyl isothiocyanate (PEITC) and sulforaphane (SFN) protect animals against chemically induced tumours. Putative chemoprotective mechanisms include modulated expression of hepatic biotransformation enzymes. However, few, if any, studies have used human primary cells as test models. 2. The present study investigated the effects of these phytochemicals on the expression of four ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…SF also induced expression of GST A1/2 isoforms and NQO1 in primary rat hepatocytes in a dose-response and time-course manner [49], although prolonged treatment was required to obtain GST induction levels comparable to those obtained in hepatoma cell lines [29]. Similar results were observed in primary cultures of freshly isolated human hepatocytes where NQO1 expression responded to SF but no significant effects on GSTA1 transcription were seen [50]. SF induced phase 2 detoxification enzymes, UDPG1A1 and GSTA1 mRNA expression in human hepatocytes, although UGT1A1 induction was subject to inter-individual variation [36].…”
Section: Induction Of Phase 2 Detoxification Enzymessupporting
confidence: 79%
“…SF also induced expression of GST A1/2 isoforms and NQO1 in primary rat hepatocytes in a dose-response and time-course manner [49], although prolonged treatment was required to obtain GST induction levels comparable to those obtained in hepatoma cell lines [29]. Similar results were observed in primary cultures of freshly isolated human hepatocytes where NQO1 expression responded to SF but no significant effects on GSTA1 transcription were seen [50]. SF induced phase 2 detoxification enzymes, UDPG1A1 and GSTA1 mRNA expression in human hepatocytes, although UGT1A1 induction was subject to inter-individual variation [36].…”
Section: Induction Of Phase 2 Detoxification Enzymessupporting
confidence: 79%
“…It has been shown that PEITC induces the expression of several xenobiotic-metabolizing CYPs which could potentially activate carcinogens. In cultured human primary hepatocytes, it was also shown that PEITC dose-dependently upregulated the expression of carcinogen-activating enzymes CYP1A1 and CYP1A2 using quantitative polymerase chain reaction analyses (20). On the other hand, activities of CYPs have been shown to be inhibited by PEITC.…”
Section: Inhibition Of Phase I Cyp Dmesmentioning
confidence: 99%
“…Studies in animals have shown that natural products present in food and herbal drugs will induce synthesis of P450 isoforms in the 1, 2 and 3 families (Table 1). Phytochemicals known to induce CYP1A1 and CYP1A2 synthesis include isothiothiocyanates, indole-3-carbinol and its condensation products (including di-indolylmethane), flavonoids and tea polyphenolic compounds (Gross-Steinmeyer et al, 2004;Moon et al, 2006). The herbal drug, St. John's wort, which has the active component, hyperforin, induces hepatic CYP3A4 (Komoroski et al, 2004).…”
Section: Effects Of Food Natural Products On Cytochrome P450 Concentrmentioning
confidence: 99%